2013
DOI: 10.5897/jpp2013.0271
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic and hypoglycemic studies of Achyranthus aspera L.

Abstract: In the present study, the ethanolic extract of Achyranthus aspera L. Leaves (EEA) were investigated for their pharmacognostic characteristics and hypoglycemic effects. The pharmacognosy of the plant was carried out using microscopic and macroscopic tools. Macroscopic studies revealed that the leaves were cauline, ramel, opposite, exstipulate, simple, sub-sessile, ovate, entire, acute, unicostate, reticulate, rough, coriaceous and hairy. The stem was erect, herbaceous, quadrangular, branched, solid, green and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The chemical constituents of A. bidentata include oleanolic acid glycosides, saponins, ecdysterone, ketosteroids, and flavonoids [6]. Although modern pharmacological studies have shown that A.bidentata has a plethora of bio-activities, including anti-osteoarthritis [7], improving memory [8], regulating blood sugar level [9], preventing apoptosis [10], promoting angiogenesis, UV protection [11], anti-convulsion [12], anti-osteoporosis [13], improving xerophthalmia [14], and alleviating acute kidney injury [15], this herb is commonly used in the clinical treatment of osteoarthritis. After being salt-processed, the effects will be dramatically enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical constituents of A. bidentata include oleanolic acid glycosides, saponins, ecdysterone, ketosteroids, and flavonoids [6]. Although modern pharmacological studies have shown that A.bidentata has a plethora of bio-activities, including anti-osteoarthritis [7], improving memory [8], regulating blood sugar level [9], preventing apoptosis [10], promoting angiogenesis, UV protection [11], anti-convulsion [12], anti-osteoporosis [13], improving xerophthalmia [14], and alleviating acute kidney injury [15], this herb is commonly used in the clinical treatment of osteoarthritis. After being salt-processed, the effects will be dramatically enhanced.…”
Section: Introductionmentioning
confidence: 99%